2020
DOI: 10.13181/mji.oa.193306
|View full text |Cite
|
Sign up to set email alerts
|

Association between axillary lymph node involvement and clinicopathological features of breast cancer among Indonesian women

Abstract: BACKGROUND Some clinicopathological features play roles in the spread of breast cancer to axillary lymph node (ALN). However, their roles as predictive factors are not well-established. This study was conducted to determine the correlation between the clinicopathological features of breast cancer and the risk of ALN involvement in Indonesian women. METHODS This cross-sectional study was conducted in Margono Soekarjo Hospital using archival data from January 2017 to June 2018. All subjects with breast can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…9 Novrial D et al also reported grade II with the most number of 69 cases. 15 Agnani B et al reported grade I and grade II with the same number of 15 cases each. 19 Sener et al found the most LVI in 82 cases.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…9 Novrial D et al also reported grade II with the most number of 69 cases. 15 Agnani B et al reported grade I and grade II with the same number of 15 cases each. 19 Sener et al found the most LVI in 82 cases.…”
Section: Discussionmentioning
confidence: 97%
“…14 Research Novrial D et al also reported tumor size >2-≤5 cm in 56 cases and stage I in 47 cases. 15 Research by Chen Z et al reported stages I and II in 35 cases, tumor size >2 cm in 33 cases, positive lymph node metastases in 27 cases. 16 Sener et al reported a tumor size of 2-5 cm in 60 cases and found no KGB involvement in 28 cases.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Unilateral breastfeeding is not unheard of, but the literature largely discusses this in relation to maternal factors such as unilateral mastectomy (Baslaim et al, 2011;Ko et al, 2013;Barco et al, 2015). This is notable as unilateral breastfeeding due to infant breast preference is a risk factor for early cessation of breastfeeding and may also be a risk factor for breast cancer in the unsuckled breast (Novrial et al, 2020). There is no literature available relating to breast preference due to medical devices or how to overcome this.…”
Section: Difficulties Indirectly Related To the Child's Conditionmentioning
confidence: 99%